Teachers’ Speech Acts on Students’ Engagement in Indonesian EFL Classrooms - Sinta Dewi; Virna Alfiqa Sopwani; Agis Aeni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Strategic use of teacher’s language in the classroom has been acknowledged to play pivotal role in shaping the extent of students’ engagement. Despite extensive research on the subject, a limited understanding remains on the potential’s mismatch between teacher’s practice and students’ preference. This study examines how specific teacher’s speech acts, as a part of teacher’s language, influence Indonesian EFL students’ engagement and investigates which types of speech acts students perceive as most engaging. To achieve the objectives, the study collected the data through video-taped observations and a close-ended 20-item questionnaire administered to 47 junior high school students in Garut. The findings show that the teacher’s speech acts, particularly Directives, Assertives, and Expressives, exert substantial influence on the students’ behavioral, cognitive, and emotional engagement. Notably, despite the prominent role of those speech acts in fostering engagement during classroom interaction, students' self-reported preferences through questionnaires indicated that Expressives and Declarations were perceived as the most engaging. This discrepancy suggests that while teachers predominantly use instructional speech acts (e.g., Directives and Assertives), students exhibit a stronger affinity to Expressives and Declarations, which often incorporate elements of emotional connection, motivation, and humor. These findings reinforce the necessity for a balanced and dynamic pedagogical approach in EFL settings, by integrating various speech acts to optimize students’ engagement.